2021
DOI: 10.1097/md.0000000000024685
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative spinal epidural hematoma in a biportal endoscopic spine surgery

Abstract: Biportal endoscopic spine surgery (BESS) is extending its application to most kind of spine surgeries. Postoperative spinal epidural hematoma (POSEH) is one of the major concerns of this emerging technique. Through this study we aim to investigate the incidence of POSEH in BESS comparing to a conventional spine surgery (CSS). The patients who underwent a non-fusion decompressive spine surgery due to degenerative lumbar spinal stenosis (LSS) or herniated lumbar disc (HLD) or both between January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…In BESS, in the prone position, 2 unilateral portals (1 for endoscopy and the other for instrumental working) were made. [ 4 ] We used a saline infusion pump with a pressure of 50 mm Hg, which is higher than the average venous pressure of 40 mm Hg to prevent venous bleeding. [ 4 ] A vacuum suction drain was placed and connected to a negative pressure bag of 120 ± 30 mm Hg in all cases, and it was removed on day 2 after the operation.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In BESS, in the prone position, 2 unilateral portals (1 for endoscopy and the other for instrumental working) were made. [ 4 ] We used a saline infusion pump with a pressure of 50 mm Hg, which is higher than the average venous pressure of 40 mm Hg to prevent venous bleeding. [ 4 ] A vacuum suction drain was placed and connected to a negative pressure bag of 120 ± 30 mm Hg in all cases, and it was removed on day 2 after the operation.…”
Section: Methodsmentioning
confidence: 99%
“…[ 4 ] A vacuum suction drain was placed and connected to a negative pressure bag of 120 ± 30 mm Hg in all cases, and it was removed on day 2 after the operation. [ 4 ]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the start of UBE/BESS technology, the overall number of published studies had shown a steady growth trend, which indicated that UBE/BESS technology research had entered a stage of rapid development and maintained a high degree of heat. As a new surgical technique, UBE/BESS had a short history and less published literature 7,[15][16][17][18] . Literature research showed that only 13 countries and regions had paid attention to it.…”
Section: Characteristics Of National Productivity Of Ube/bessmentioning
confidence: 99%